Assesment of pain management in chronic pancreatitis after lateral pancreatico-jejunostomy: A comparative analysis of pre and post operative outcomes - Islam, Mohammad Jayedul; Suma, SA; Farhad Ul Hassan , ASM; Hoque, AMK; Daisy, NS; Khan, MS (Journal of Shaheed Suhrawardy Medical College, 2024)
Background: Chronic pancreatitis is a fairly common condition with pain being the major symptom and lateral pancreaticojejunostomy (LPJ) is performed for symptomatic relief. It is done for patients with severe pain, obstructed and dilated pancreatic duct. Surgical decompression of the duct and ductal drainage can achieve best pain relieve and slow the progression of the disease. Aim: The aim of the study was to assess relief of pain pre and post-LPJ for chronic pancreatitis. Methods: This prospective observational study was conducted at the Department of Surgery in Shaheed Suhrawardy Medical College Hospital, for One year period. Patients with chronic pancreatitis admitted in the department of surgery were approached for inclusion in the study. Total 17 patients were selected according to inclusion and exclusion criteria. Informed written consent was taken from each patient. All patients underwent lateral Pancreaticojejunostomy. Detail clinical and demographic history was taken along with thorough physical examination relevant investigations. All patients were evaluated preoperatively and post operatively at discharge, 1 month and 3 months. Pain was assessed preoperatively and post operatively using Visual analogue scale (VAS). Collected data were checked and analysed in SPSS 23. Results: Among 17 patients, average age was 33.4 (±9.6) years with majority in age group 20-35 years. Male patients were more than female (67% vs 33%). Major clinical presentations upper abdominal pain (100%), nausea/vomiting (73.3%), history of weight loss (60%), fatigue (53.3%), fever (40%), steatorrhoea (40%), diarrhoea (33.3%) and shortness of breathe (26.7%). Among 73.3% patients, outcome was good and among 26.7% patients, outcome was poor. Of all, 40% had VAS score 0 at discharge but increased at 1 months (53.3%) and 3 months (73.3%) follow up and 26.7% had higher VAS score at discharged reached but to a VAS score of 0 or 2 at 1 month (6.7%) and 3 months (6.7%) follow up. Mean pain score before and after the lateral pancreaticojejunostomy surgery was 8.26±1.27 and 1.7±1.66 with statistically significance (p <0.001). Conclusion: Seventy Three percent of patients had good outcome regarding pain after LPJ. Significant relief in symptoms of pain were noted after LPJ. Further larger study is recommended to validate this findings. J Shaheed Suhrawardy Med Coll 2022; 14(2): 39-46